Metabolic Basis for Thyroid Hormone Liver Preconditioning: Upregulation of AMP-Activated Protein Kinase Signaling - Luis A. Videla; Virginia Fernández; Pamela Cornejo; Romina Vargas (The Scientific World Journal)
The liver is a major organ responsible for most functions of cellular metabolism and a mediator between dietary and endogenous sources of energy for extrahepatic tissues. In this context, adenosine-monophosphate- (AMP-) activated protein kinase (AMPK) constitutes an intrahepatic energy sensor regulating physiological energy dynamics by limiting anabolism and stimulating catabolism, thus increasing ATP availability. This is achieved by mechanisms involving direct allosteric activation and reversible phosphorylation of AMPK, in response to signals such as energy status, serum insulin/glucagon ratio, nutritional stresses, pharmacological and natural compounds, and oxidative stress status. Reactive oxygen species (ROS) lead to cellular AMPK activation and downstream signaling under several experimental conditions. Thyroid hormone (L-3,3′,5-triiodothyronine, T3) administration, a condition that enhances liver ROS generation, triggers the redox upregulation of cytoprotective proteins affording preconditioning against ischemia-reperfusion (IR) liver injury. Data discussed in this work suggest that T3-induced liver activation of AMPK may be of importance in the promotion of metabolic processes favouring energy supply for the induction and operation of preconditioning mechanisms. These include antioxidant, antiapoptotic, and anti-inflammatory mechanisms, repair or resynthesis of altered biomolecules, induction of the homeostatic acute-phase response, and stimulation of liver cell proliferation, which are required to cope with the damaging processes set in by IR.